Fork‐shaped patch printed ultra‐wideband slot antenna with dual band‐notched characteristics using metamaterial unit cells. Issue 7 (28th March 2019) - Xu, Bihui; Zhao, Yanwen; Gu, Li; Nie, Zaiping
Abstract: In this article, a miniaturized fork‐shaped patch ultra‐wideband (UWB) planar wide‐slot antenna with dual band‐notched characteristics is proposed. With fork‐shaped patch, ultra‐wideband impedance matching from 3.1 to 13.2 GHz is easily achieved. Then, two novel and simple methods are applied to solve the difficulty for UWB slot antennas with fork‐shaped patch to realize band‐notched characteristics. By etching one pair of I‐shaped resonators on both branches of the fork‐shaped structure and adding a rectangular single split‐ring resonator in the rectangular openings of fork‐shaped patch, the wireless local area network (WLAN) band from 5.5 to 6.1 GHz and the International Telecommunication Union (ITU) 8 GHz band from 7.9 to 8.7 GHz are rejected, respectively. The coplanar waveguide‐fed UWB antenna is successfully designed, fabricated, and measured. The measured and simulated results show a good agreement. The antenna provides nearly stable radiation patterns, high gains and high radiation efficiency.